RELEVANSI TEORI HUMANITARIAN INTERVENTION DALAM PERSPEKTIF ISLAM - Julia Rizky Utami (The Indonesian Islamic Studies and International Relations Association (Insiera), 2016)
This article explains the relevance of humanitarian intervention theories in Islamic perspective containing analytical writings on ontological, epistemological, and axiological aspects. Todays humanitarian intervention theories are similar to Islamic thought in its humanity aspects. Islam teaches about karomah insaniyah or known as human dignity. The developed humanitarian intervention theories have the same ideas with Islamic values. Islam teaches that intervention is justified by morality principles as well as to guarantee human rights of the citizens in the conflicting state or victims in the disasters. Therefore, the writer assumes that humanitarian intervention theories are relevant to Islamic values.